Effective Finite Element Solution and Post-Processing for Wide Load Spectrum - Handrik, Marian; Vasko, Milan; Kopas, Peter; Saga, Milan (Communications - Scientific letters of the University of Zilina, 2014)
This paper presents a computational algorithm allowing the efficient use of high-performance computing resources to solve nonlinear problems of continuum mechanics using FEM. The algorithm is suitable for solving static problems and tasks of estimating lifetime of structures in cases where the load is defined by the load spectrum. The complexity of the problem increases significantly in the case of nonlinear problems. The principle of the stress superposition cannot be used in that case. For each loading mode a separate FE analysis must be made. A quick and efficient procedure for evaluating the results of mentioned analysis for the static calculation as well as for the estimated life calculation is also presented in this paper. In the presented examples the contact of bodies is used as a source of nonlinearity. The size, shape or position of the contact area is not possible to estimate in contact of bodies. These types of problems are thus highly nonlinear. Programs for the presented algorithms are processed in the program package OCTAVE and calculations using FEM are made in the software ADINA.